Community-based mechanisms underlying the root cadmium uptake regulated by Cd-tolerant strains in rice (Oryza sativa. L) - Li, Peng; Xiong, Ziqin; Tian, Yunhe; Zheng, Zhongyi; Liu, Zhixuan; Hu, Ruiwen; Wang, Qiming; Ao, Hejun; Yi, Zhenxie; Li, Juan (Frontiers in Plant Science, 2023)
In recent years, the problem of Cd pollution in paddy fields has become more and more serious, which seriously threatens the safe production of food crops and human health. Using microorganisms to reduce cadmium pollution in rice fields is a green, safe and efficient method, the complicated interactions between the microbes in rice roots throughout the process of cadmium absorption by rice roots are poorly understood. In this investigation, a hydroponic pot experiment was used to examine the effects of bacteria R3 (Herbaspirillum sp) and T4 (Bacillus cereus) on cadmium uptake and the endophytic bacterial community in rice roots. The results showed that compared with CK (Uninoculated bacterial liquid), the two strains had significant inhibitory or promotive effects on cadmium uptake in rice plant, respectively. Among them, the decrease of cadmium content in rice plants by R3 strain reached 78.57-79.39%, and the increase of cadmium content in rice plants by T4 strain reached 140.49-158.19%. Further investigation showed that the cadmium content and root cadmium enrichment coefficient of rice plants were significantly negatively correlated with the relative abundances of Burkholderia and Acidovorax, and significantly positively correlated with the relative abundances of Achromobacter, Agromyces and Acidocella. Moreover, a more complex network of microbes in rice roots inhibited rice plants from absorbing cadmium. These results suggest that cadmium uptake by rice plants is closely related to the endophytic bacterial community of roots. This study provides a reference scheme for the safe production of crops in cadmium contaminated paddies and lays a solid theoretical foundation for subsequent field applications.